Management of Arrhythmias in COVID-19 - Yusuf Ziya Şener; Uğur Canpolat; Hikmet Yorgun; Kudret Aytemir (Eurasian Journal of Emergency Medicine, 2022)

(untitled)
Coronavirus disease-2019 (COVID-19) disease is caused by severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) virus infection and firstly appeared in China and then became a pandemic. The leading cause of mortality is respiratory failure in COVID-19; however, cardiovascular manifestations are frequent and also important causes of death in COVID-19. The incidence of arrhythmia is increased in patients with COVID-19 due to increased systemic inflammatory response, hypoxia, and administered drugs. All kinds of arrhythmias, including bradyarrhythmias, supraventricular and ventricular arrhythmias, may develop during COVID-19 course. QT prolongation plays a central role in COVID-19 related arrhythmias. Therefore, QT duration should be strictly followed. All the clinicians should know the management of arrhythmias that they might face with frequently during the pandemic.